Preliminary effects of pagoclone, a partial GABAA agonist, on neuropsychological performance - Angela F Caveney (Dove Medical Press, 2008)
Angela F Caveney1, Bruno Giordani1, George M Haig21Department of Psychiatry, University of Michigan, Ann Arbor, MI, USA; 2Neurosciences Development, Abbott Laboratories, Abbott Park, IL, USAAbstract: Pagoclone is a novel cyclopyrrolone that acts as a partial GABAA receptor agonist. Preclinical studies suggest that pagoclone may have clinical utility as an anxiolytic agent, as well as a reduced incidence of side-effects. The present study was conducted to determine whether pagoclone would affect healthy individuals’ performances on neuropsychological measures as a function of dose within the projected therapeutic range. Twelve healthy adult subjects were randomly assigned to dosage groups in a 3-way crossover study. Participants were administered neuropsychological measures six hours following dosing on Day 1 and Day 6 of administration of the drug. Dose effects were noted on measures of alertness, learning, and memory and movement time. Significant effects were also noted on measures of alertness, learning and memory, information processing and psychomotor speed. Overall, the results of this small, preliminary study do not support a finding of behavioral toxicity for these doses of pagoclone. Rather, a pattern was found of transient and mild negative effects on learning and memory scores at the highest dose administered, though these changes were small and no longer evident by the sixth day of use.Keywords: pagoclone, cyclopyrrolone, neuropsychological, memory, generalized anxiety disorder